Therapeutic Potential of Ethanol Extract from Durian Peel on Testes Microanatomy in Diabetic Male Rats - Syakera, Cinta Etna; Isdadiyanto, Sri; Sunarno , Sunarno; Ermanjaya, Laode (Universitas Negeri Semarang, 2025)
Diabetes mellitus (DM) is a degenerative disease that can lead to complications such as testicular atrophy. As DM requires lifelong treatment, natural and safe therapeutic alternatives are needed. Durian peel, as a natural material, has potential. This study investigated the effects of ethanol extract of durian peel (EEDP) on testicular histology in diabetic rats. A total of 25 male Sprague-Dawley rats, aged 2 months and weight ±200 g, were randomly assigned to five groups: healthy (K0), diabetic (K1), and diabetic+EEDP at doses of 500 (K2), 750 (K3), and 1,000 mg/kgBW (K4), given orally for 28 days. After treatment, the rats were euthanized, and their testes were removed, weighed, and examined using hematoxylin-eosin staining. Observed variables included testis weight, seminiferous tubule diameter, epithelial thickness, and spermatogenesis stages. Statistical analysis ANOVA (α=0,05) showed significant improvements (p < 0,05) in the EEDP-treated groups. It is concluded that EEDP at doses of 500-1,000 mg/kgBW improved testicular structure in diabetic rats.. The novelty of this study lies in the utilization of durian peel ethanol extract at varying doses of 500–1,000 mg/kgBW as a natural therapy to improve testicular histological damage caused by diabetes. This study serves as a basis for the development of herbal antidiabetic drugs with protective effects on the reproductive system. The findings are expected to contribute to biomedical science and provide opportunities for utilizing durian peel waste as a value-added material for public health.